PENGEMBANGAN MEDIA PEMBELAJARAN PSYCHOLOGICAL FIRST AID: LANGKAH AWAL MEREDAM SELF-HARM - Edy, Dewi Fatmasari; Nurmalita, Femmi; Febrianti, Widi; Nadzifah, Naurah (Universitas Tribhuwana Tunggadewi, 2024)
This development research aims to create digital-based learning content on psychological first aid as a first step to reduce self-harm behaviour as an effort to provide psychological support in crisis situations. This is due to the rampant cases of mental disorders that lead to self-harm. This learning media development uses the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The data analysis used was descriptive analysis of the trial results and the effectiveness of the media conducted through a survey to 57 students regarding the understanding and user response to the media developed using 8 (indicators) of assessment. Digital learning media produced in the form of educational content uploaded through massive online open courses and also through 2 (two) social media, namely YouTube and Instagram. All respondents gave an assessment that their understanding of PFA and self-harm increased after reading and watching the educational videos presented. Digital learning media can be an effective tool in educating mental health, including PFA to deal with self-harm. Recommendations and suggestions for further development are to expand the target audience and conduct further research to assess the long-term impact of media on self-harm management.